Physicochemical characterization of thermodynamic parameters and ısomer separation of Hemin by ınverse gas chromatography - Cakar, Ayse Erdogan (SPRINGER HEIDELBERG, 2026)
This study examines the retention behavior of various polar and non-polar probes on hemin, which is employed as a stationary phase, using the inverse gas chromatography (IGC) technique at infinite dilution. By utilizing the retention behaviour of the probes on hemin, thermodynamic parameters such as The Flory-Huggins interaction parameters (\documentclass[12pt]{minimal} \usepackage{amsmath} \usepackage{wasysym} \usepackage{amsfonts} \usepackage{amssymb} \usepackage{amsbsy} \usepackage{mathrsfs} \usepackage{upgreek} \setlength{\oddsidemargin}{-69pt} \begin{document}$$\:{\chi\:}_{12} {\infty\:}$$\end{document}) and mole fraction activity coefficients (\documentclass[12pt]{minimal} \usepackage{amsmath} \usepackage{wasysym} \usepackage{amsfonts} \usepackage{amssymb} \usepackage{amsbsy} \usepackage{mathrsfs} \usepackage{upgreek} \setlength{\oddsidemargin}{-69pt} \begin{document}$$\:{{\upgamma\:}}_{1} {\infty\:}$$\end{document}) were determined by IGC in a temperature range of 125-150 degrees C. The results obtained showed that all the probes were poor solvents for hemin. In addition, the dispersive surface energy (\documentclass[12pt]{minimal} \usepackage{amsmath} \usepackage{wasysym} \usepackage{amsfonts} \usepackage{amssymb} \usepackage{amsbsy} \usepackage{mathrsfs} \usepackage{upgreek} \setlength{\oddsidemargin}{-69pt} \begin{document}$$\:{\gamma\:}_{S} {D}$$\end{document}) of Hemin was determined in the range of 30-55 degrees C. For this, the Doris-Gray method (39.13 to 44.65 mJ/m2), the Schultz method (36.06 to 42.97 mJ/m2), Hamieh 1 (44.95 to 52.04 mJ/m2) and Hamieh 2 (44.20 to 54.15 mJ/m2) method were used. Furthermore, the specific free enthalpy of the solvents on the hemin was determined. With the obtained data, it was determined that the hemin surface showed an acidic structure compared to the classical (\documentclass[12pt]{minimal} \usepackage{amsmath} \usepackage{wasysym} \usepackage{amsfonts} \usepackage{amssymb} \usepackage{amsbsy} \usepackage{mathrsfs} \usepackage{upgreek} \setlength{\oddsidemargin}{-69pt} \begin{document}$$\:{K}_{D}/{K}_{A}=0.30$$\end{document}), Hamieh 1 (\documentclass[12pt]{minimal} \usepackage{amsmath} \usepackage{wasysym} \usepackage{amsfonts} \usepackage{amssymb} \usepackage{amsbsy} \usepackage{mathrsfs} \usepackage{upgreek} \setlength{\oddsidemargin}{-69pt} \begin{document}$$\:{K}_{D}/{K}_{A}=0.22$$\end{document}) and Hamieh 2 methods (\documentclass[12pt]{minimal} \usepackage{amsmath} \usepackage{wasysym} \usepackage{amsfonts} \usepackage{amssymb} \usepackage{amsbsy} \usepackage{mathrsfs} \usepackage{upgreek} \setlength{\oddsidemargin}{-69pt} \begin{document}$$\:{K}_{D}/{K}_{A}=0.19$$\end{document}). Furthermore, the ability of Hemin to separate various series of isomers was investigated in the range of 30-55 degrees C and it was observed that hemin performed separation of these series of isomers.
Keywords: Hemin; Inverse gas chromatography; Isomer separation; Thermodynamic parameters; FREE-ENERGY CHARACTERISTICS; ACID-BASE PROPERTIES; SHORT GLASS-FIBERS; MOLECULAR PROBES; SOLID CHROMATOGRAPHY; INFINITE DILUTION; TOPOLOGICAL INDEX; SURFACE; ADSORPTION; COEFFICIENTS; Engineering